Stochastic dominance and applications to finance, risk and economics - Songsak Sriboonchitta (CRC Press, 2010)
A guide that helps readers build a useful repertoire of mathematical tools in decision making under uncertainty, especially in investment science. It uses real data and statistical procedures, such as hypothesis testing, to show how SD theory is applied in financial situations